2017
DOI: 10.1016/j.nlm.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine improves the persistence of reconsolidated fear memory and neural differentiation in vitro: Involvement of BDNF

Abstract: Putrescine, spermidine and spermine are organic cations implicated in learning, memory consolidation, reconsolidation and neurogenesis. These physiological processes are closely related, and convincing evidence indicates that neurogenesis is implicated both, in the establishment and maintenance of remote contextual fear memory. Although brain-derived neurotrophic factor (BDNF) is a key mediator involved in both neurogenesis and memory consolidation, effects of spermidine on persistence of memory after reactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Fabbrin et al [ 133 ] reported an improvement in fear memory consolidation post spermidine treatment (2 nmol/site) given immediately after training in adult male Wistar rats, whereas ANA-12, a TrkB antagonist, inhibited the positive effect of spermidine on memory consolidation. Signor et al [ 134 ], in a series of experiments on rats to study the effect of spermidine consumption on fear memory reconsolidation and neural differentiation, noted that reconsolidated memory persistence increased in a time-dependent manner when spermidine is administered (intrahippocampal infusion (i.h.)) immediately ( p = 0.005) or 12 h ( p = 0.007) post reactivation session ( p = 0.005), as the freezing score increased to ~80% and ~65%, respectively, as compared to ~40% in the control group during the testing session conducted 7 days post reactivation.…”
Section: Nutritional Roles Of Polyamines In Health Maintenance and Disease Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabbrin et al [ 133 ] reported an improvement in fear memory consolidation post spermidine treatment (2 nmol/site) given immediately after training in adult male Wistar rats, whereas ANA-12, a TrkB antagonist, inhibited the positive effect of spermidine on memory consolidation. Signor et al [ 134 ], in a series of experiments on rats to study the effect of spermidine consumption on fear memory reconsolidation and neural differentiation, noted that reconsolidated memory persistence increased in a time-dependent manner when spermidine is administered (intrahippocampal infusion (i.h.)) immediately ( p = 0.005) or 12 h ( p = 0.007) post reactivation session ( p = 0.005), as the freezing score increased to ~80% and ~65%, respectively, as compared to ~40% in the control group during the testing session conducted 7 days post reactivation.…”
Section: Nutritional Roles Of Polyamines In Health Maintenance and Disease Preventionmentioning
confidence: 99%
“…Additionally, in vitro studies revealed that as a consequence of spermidine treatment (10 nM), the migration of neurons increased on day 1 of differentiation, while neurites count increased on day 7 of differentiation of neural progenitor cells (NPCs) without affecting their length. Signor et al [ 134 ] reported the involvement of GluN2B-containing N -methyl-D-aspartate (NMDA) receptors, protein synthesis, and role of protein kinase A (PKA) pathway in increasing persistence of fear memory when spermidine is administered (i.h.) 12 h after training.…”
Section: Nutritional Roles Of Polyamines In Health Maintenance and Disease Preventionmentioning
confidence: 99%
“…In agreement with these results, reactivation-induced fear conditioning memory enhancement requires hippocampal BDNF expression in stressed rats (Giachero et al, 2013). Also, post-retrieval intra-CA1 spermidine administration lengthens contextual fear memory duration through a mechanism that depends on hippocampal BDNF maturation as well as on the interaction between this neurotrophin and its main receptor, tropomyosin-related receptor kinase B (TrkB; Signor et al, 2017). Further, increased BDNF mRNA and protein levels as well as TrkB activation in the insular cortex accompany hippocampus-independent conditioned taste aversion (CTA) memory retrieval, and interfering with BDNF synthesis in this cortex after reactivation causes amnesia.…”
Section: Bdnf and Memory Reconsolidationmentioning
confidence: 99%
“…In this respect, it was recently proposed that enhancing reconsolidation of extinction memory could be a viable strategy to avoid its decay (Radiske et al, 2015; Rosas-Vidal et al, 2015). Findings from the last decade show that BDNF modulates reconsolidation of both aversive and extinction memories (Wang et al, 2012; Giachero et al, 2013; Radiske et al, 2015; Signor et al, 2017). Overall, these studies suggest that drugs interfering with BDNF signaling during reconsolidation of aversive memories could help to impair its retention, while approaches that activate BDNF/TrkB pathways after extinction memory retrieval may promote its persistence, preventing reappearance of the fear response.…”
Section: Implications Of Bdnf Signaling Manipulation During Memory Rementioning
confidence: 99%
“…Beyond its longevity-extending effects, spermidine has rather broad health-promoting effects. Thus, it improves diastolic function of the aging heart, prevents heart failure driven by salt-induced hypertension [2], improves the efficacy of anticancer immunotherapies [9,10], increases cognition [11], halts inflammation [12], reduces liver fibrosis and nonalcoholic fatty liver disease (NAFLD) [6,13], and prevents high-fat diet (HFD)-induced obesity and diabetes [14]. Many of these effects depend on the induction of autophagy [5,6,9,10,14].…”
Section: Introductionmentioning
confidence: 99%